PARADIGMA SUNNI TAFSIR KH. AHMAD BASYIR (1930-2017) DALAM PERSPEKTIF TEKSTUALITAS GRACIA - Mahmudi Mahmudi; Moh. Wardi (Lajnah Pentashihan Mushaf Al-Qur'an, 2021)
This article analyzes the local interpretation of the Qur’an of Madura which was written by KH Ahmad Basyir (1930-2017) who was considered a figure and scholar of his time. Ahmad Basyir is a highly respected figure, especially in Sumenep, even in Madura. The method in this article is a literature study with the focus on his Kitab atTafsir volume I. The author argues that the interpretation he wrote is an interpretation of the Sunni paradigm that puts the servant’s ethics first in his relationship with God. In the process of analysis, the author uses the perspective of Gracia’s textuality and tries to seek its relevance to the reality of Indonesia today. The author assumes that Ahmad Basyir’s interpretation style offers a relevant understanding of Islam in the midst of the spread of religious radicalism.